ENVIRONMENTAL IMPACT COMPARISON OF INDIVIDUAL AND PUBLIC TRANSPORT (Perner's Contacts, 2010)
This contribution deals with assessment of emissions of individua and public transport.
Keywords: emissions; transportation; emission standards; environmental impact